UPAYA PENINGKATAN MUTU SEKOLAH DENGAN STRATEG BAURAN PEMASARAN UNTUK KEPUASAN PELANGGANPADA SMP MUHAMMADIYAH SINAR FAJAR CAWAS DAN SMPIT MUHAMMADIYAH AN NAJAH JATINOM KLATEN - Agus Mulyadi; Eko Supriyanto; M Muthoifin; Sudarno Shobron (Universitas Muhammadiyah Surakarta, 2020)
Education is an important thing in life, currently, the education sector is becoming a marginalized part. The right strategy is needed so that the world of education is more advanced and quality. Muhammadiyah Middle School Sinar Fajar Cawas and Muhammadiyah Integrated Islamic Middle School An Najah Jatinom is a new school whose existence has received a good response from the community. The school applies a marketing mix strategy to improve the quality of schools. This research was carried out aiming to find out the steps, supporting and inhibiting factors in the implementation of the Marketing Mix strategy in the Muhammadiyah Junior High School, Sinar Fajar Cawas and in the Integrated Islamic Middle School Muhammadiyah An Najah Jatinom Klaten. This research uses field research methods. Data obtained by observation, interview, and documentation. The steps that have been taken in implementing the Marketing Mix strategy to improve the quality of schools in Muhammadiyah Junior High School Sinar Fajar Cawas and Muhammadiyah Integrated Islamic Middle School An Najah Jatinom Klaten is by applying the 7P step, the step includes, the Product (product) in the form of a variety of selected programs. Price (price), in the form of school fees offered to student guardians with a payment system, can be done directly or via transfer. Place, strategic locations of both schools can be reached by public and private transportation. Promotion is carried out through print, electronic and social media. People (human resources) include educators and education staff who are young and enthusiastic. Physical evidence in the form of school buildings and student learning outcomes reports. Process, the implementation of education in the two schools has met the national education standards. Supporting factors in the implementation of the Marketing Mix strategy at the Muhammadiyah Junior High School Sinar Fajar Cawas are high public interest, educators (teachers) who are still young, passionate and have high creativity, varied programs, educative figures that are represented by prospective students and parents of students. The inhibiting factors in the implementation of the Marketing Mix strategy in Muhammadiyah Sinar Fajar Junior High School are, the lack of school facilities and infrastructure, the network outside of school which is still minimal, and the limited human resources in terms of quantity and quality. Supporting factors in the implementation of the Marketing Mix strategy at An Najah Jatinom Integrated Islamic Middle School are high public interest, young educators (teachers), enthusiasm and high creativity, good, comfortable, and attractive school buildings, and varied programs. The inhibiting factors in the implementation of the Marketing Mix strategy at Muhammadiyah Integrated Islamic Middle School An Najah Jatinom are, the teaching staff is still minimal in terms of quantity and quality, the school is less consistent in program implementation and the lack of learning support facilities